Evaluasi Tingkat Kelayakan Sistem Informasi Akademik Perguruan Tinggi dengan Framework ISO/IEC 27001:2013 - Anas, Andi Sofyan; Tajuddin, Muhammad; Adil, Ahmat; Hammad, Rifqi (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
One university that has made use of information technology to provide high-quality services for students and the academic community as a whole is X University. Information Technology and Communication Center (PUSTIK), which is in charge of carrying out the creation, management, service, and upkeep of information and communication technology security, is in charge of overseeing this information technology service. Information security should be able to be maintained by effective IT governance. As a result, it's critical to assess information system security, particularly that of academic information systems. The ISO/IEC 27001:2013 standard is cited in Indeks Keamanan Informasi (KAMI), which is used in this information system security evaluation to assess the maturity level of information security. An assessment of five areas The Information Security Risk Management category receives the lowest score of 10 out of a possible 72 according to the KAMI Index. With a total score of 166, the KAMI Index dashboard results indicate that each area of information security maturity is at levels I and I+. This indicates that the ISO 27001:2013 standard's level of implementation completeness falls into the insufficient category.